A3.05 The lung microbiome in rheumatoid arthritis and associated local/systemic autoimmunity. (24th February 2016) - Joshua, V; Scher, JU; Ubeda, C; Artacho, A; Segal, L; Grunewald, J; Catrina, AI
Abstract : Background and objectives: Airway abnormalities and increased lung tissue citrullination is found in both RA patients and individuals at at-risk for the development of disease. Recent data suggest that the gut (Prevotella copri) and oral (Porphyromonas gingivalis) microbiome might potentially contribute to the priming of an aberrant systemic immune response characteristic of RA. Our objective was to study whether the RA lung microbiome contains distinct taxonomic features associated with local and/or systemic autoimmunity. Materials and methods: Bronchoalveolar lavage (BAL) samples from 20 subjects with RA, 10 with sarcoidosis (DC) and 24 healthy controls (HC) were obtained by research bronchoscopy. 16S rDNA sequencing was performed to define microbiota composition. Autoantibodies, including anti-CCP, RF and ACPAs were also measured in sera of RA subjects. Statistical analysis was performed using wilcoxon test and Spearman correlation. Results: The16S sequencing data showed similar alpha/beta diversity between RA and DC groups, but significantly different from HC. Taxonomic comparison between groups was performed using LEfSe, which revealed several significant differences (LDA score>2). Multiple taxa, including Rhanella and Rhodanobacter were present only in the RA and DC groups, but completely absent from HC (p < 0.001). While RA BAL samples were enriched with Sphingobacteria, sarcoidosis BAL was enriched with Bacteroidia, Rhizobiales, Nitrospirales, and Campylobacter. Raoultella and Barnesiella correlated with CCP2 levels in BAL (rho = 0.49 and 0.47; p-value = 0.026 and 0.032). Serum levels of CCP-IgA had a negative correlation with Massilia and Tannerella (rho = -0.63 and 0.53; p-value 0.003 and 0.016), and a positive correlation with Vagococcus and Lactobacillus (rho= 0.59 and 0.54; p-value 0.006 and 0.014). Unclas_Lactobacillales also had a positive correlation with serum levels of RF-IgA (rho = 0.71; p-value <0.001). Serum levels of anti-CCP2 antibodies had a positive correlation with Porphyromonas, Rahnella and Chryseobacterium (rho =0.46, 0.46 and 0.45; p-value = 0.03, 0.03 and 0.04). Conclusions: Despite the relatively small number of samples analysed, several taxonomic differences were noted between groups. Correlations between relative abundance of specific taxa in RA BAL with serum autoantibodies (ie, anti-CCP) support an association between the lung microbiome and the host immune phenotype in RA. Further evaluation of functional aspects of this microbiome may provide further insights into its possible contribution to RA.